Mutual funds : portfolio structures, analysis, management, and stewardship - Haslem, John A. (Robert W. Kolb series in finance., 2010)
An authoritative, must-read guide to making more informed decisions about mutual funds. Providing a balance of theory and application, this authoritative book will enable you to evaluate the various performance and risk attributes of mutual funds. It covers a broad range of topics, including understanding the advantages and disadvantages of mutual funds, evaluating stock/bond allocations within fund portfolios, assessing fund diversification risk, measuring fund returns and risk, and making fund buy/sell decisions. While informative chapters combine clear summaries of existing research with pr.